2016
DOI: 10.1503/cmaj.160050
|View full text |Cite
|
Sign up to set email alerts
|

Association between resting heart rate and coronary artery disease, stroke, sudden death and noncardiovascular diseases: a meta-analysis

Abstract: Background:Resting heart rate is linked to risk of coronary artery disease, stroke, sudden death and noncardiovascular diseases. We conducted a meta-analysis to assess these associations in general populations and in populations of patients with hypertension or diabetes mellitus. Methods:We searched PubMed, Embase and MEDLINE from inception to Mar. 5, 2016. We used a random-effects model to combine studyspecific relative risks (RRs). We used restricted cubic splines to assess the dose-response relation. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
68
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(74 citation statements)
references
References 62 publications
3
68
1
2
Order By: Relevance
“…The evidence on whether a decrease in RHR over time is associated with lower mortality is inconsistent 17–19. Among the few studies that have assessed the association between temporal changes in RHR and all-cause mortality, some failed to adjust for important confounders like physical activity, alcohol consumption and diet; a meta-analysis found that the association of RHR with cancer mortality was almost twofold higher in less adjusted studies, compared with those including more confounders 12. Some studies were sex-specific or disease-specific,7 19 and others assessed only short-term RHR changes (eg, over weeks/months) 19…”
Section: Introductionmentioning
confidence: 99%
“…The evidence on whether a decrease in RHR over time is associated with lower mortality is inconsistent 17–19. Among the few studies that have assessed the association between temporal changes in RHR and all-cause mortality, some failed to adjust for important confounders like physical activity, alcohol consumption and diet; a meta-analysis found that the association of RHR with cancer mortality was almost twofold higher in less adjusted studies, compared with those including more confounders 12. Some studies were sex-specific or disease-specific,7 19 and others assessed only short-term RHR changes (eg, over weeks/months) 19…”
Section: Introductionmentioning
confidence: 99%
“…Связь между ЧСС покоя и риском общей и сердечно-сосудистой (СС) смертности исследовалась за последние четверть века во многих эпидемиологических и популяци-онных исследованиях, причем как у лиц без СС патологии, так и у пациентов с различными заболеваниями сердца [28][29][30][31]. Общим выводом абсолютно всех исследований можно считать наличие прямой связи между повышением ЧСС и увеличением риска смерти.…”
Section: обзоры §unclassified
“…Более сложным явля-ется ответ на вопрос: какова оптимальная ЧСС покоя? Для здоровых лиц, как это было показано во французском регистре, повышение риска смерти начинается с ЧСС более 55-60 уд / мин [30][31][32]. Аналогичные результаты были получены и при исследовании пациентов с дока-занной коронарной болезнью сердца [33] и перенесших острый ИМ [34].…”
Section: обзоры §unclassified
“…As increased resting heart rate is associated with increased risk of cardiovascular mortality, Juhl et al concluded that increased heart rate is a potentially important and easily testable marker associated with increased risk of cardiovascular mortality and sudden death. 6 The studies about the association between HS and metabolic syndrome follow the studies about the association between psoriasis and metabolic syndrome. In 2006, the first study described the association between psoriasis and metabolic syndrome.…”
mentioning
confidence: 99%
“…Few data are available for more than 5 years of follow-up (n = 25), and recently the validity of the DLQI has been subject to a great deal of criticism. [6][7][8] …”
mentioning
confidence: 99%